A new family of MMSE multiuser receivers for interference suppression in DS - Buzzi, S.
We deal with interference suppression in asynchronous direct-sequence code-division multiple-access (CDMA) systems employing binary phase-shift keying modulation. Such an interference may arise from other users of the network, from external low-rate systems, as well as from a CDMA network coexisting with the primary network to form a dual-rate network. We derive, for all of these cases, a new family of minimum mean-square-error detectors, which differ from their conventional counterparts in that they minimize a modified cost function. Since the resulting structure is not implementable with acceptable complexity, we also propose some suboptimum systems. The statistical analysis reveals that both the optimum and the suboptimum receivers are near-far resistant, not only with respect to the other users, but also with respect to the external interference. We also present a blind and a recursive least squares-based, decision-directed implementation of the receivers wherein only the signature and the timing of the user to be decoded and the signaling time and the frequency offset of the external interferer are assumed known. Finally, computer simulations show that the proposed adaptive algorithm outperforms the classical decision-directed RLS algorithm
Keywords: BPSK modulation; CDMA network; DS/CDMA systems; MMSE multiuser receivers; Adaptive algorithm; Adaptive detection; Asynchronous direct-sequence code-division multiple-access.; Binary phase-shift keying; Blind detection; Blind receiver; Computer simulations; Decision-directed RLS algorithm; Decision-directed receiver; Dual-rate network; Frequency offset; Interference suppression; Low-rate systems; Minimum mean-square-error detectors; Modified cost function minimisation; Near-far resistant receivers; Optimum receiver; Recursive least squares-based receiver; Signaling time; Statistical analysis; Suboptimum receiver; Suboptimum systems; Timing; User signature decoding